Filtration Performance of Biodegradable Electrospun Nanofibrous Membrane for Sub‐Micron Particles: A Systematic Review - Sepideh Keyvani; Farideh Golbabaei; Rasoul Esmaeely Neisiany; Oisik Das; Mohammad Reza Pourmand; Saba Kalantary (Macromolecular Materials and Engineering, 2025)
Abstract Nanofiber membranes receive considerable interest recently because of their distinctive structural features, facile preparation, as well as high filtering efficiency. Due to ever‐increasing air pollution, membranes made from biodegradable materials can play a crucial part in providing purified air with minimum concerns of environmental issues after the membrane's end of service life. The purpose of this systematic review is to assess the performance of biodegradable electrospun nanofibrous membrane filters toward air sub‐micron particles. To identify relevant studies, a systematic search is carried out in major scientific search engines including PubMed, Scopus, and the Web of Science. Data extraction is used to collect the necessary information on the membranes' structural properties, as well as filtration performance metrics such as efficiency, pressure drop, and quality factor. Among the electrospun membranes derived from biodegradable polymers, the polyvinyl alcohol (PVA)‐based electrospun membranes are more effective in filtration efficiency in capturing sub‐micron particles. The results highlight that these types of membranes are effective in filtration with low energy consumption, making them more apt for air purification. The use of such membranes can supply both high filtering performance and protection of the environment.